Suicide rates and risk factors for suicide among Israeli immigrants from Ethiopia (1985-2017) - Rafael Youngmann; Nelly Zilber; Ziona Haklai; Nehama Goldberger (BMC, 2021)
Abstract Background Suicide rates among Ethiopian immigrants to Israel (EI) are relatively high. This study sought to identify suicide-risk factors in this population in order to suggest some potentially preventive measures to mental health policymakers who are struggling to prevent suicide among EI. Method Nationwide age-adjusted suicide rates were calculated for EI, Former Soviet Union immigrants (FSUI) and Israeli-born (IB) Jews by age, gender, and year of death and, for EI, by marital status and immigration period in the years 1985-2017 (1990-2017 for FSUI). Results Age-adjusted suicide rates for the period 1990-2017 confirmed the significantly higher rate among EI--3.1 times higher than for FSUI and 4.1 times higher than for IB. Similar rates were obtained for both genders, within each age group, and in all study years. Comparable male/female rate ratios were found among EI and IB (3.3, 3.6, respectively). Over the years of the study, only among the Ethiopian immigrants were there large fluctuations in suicide rates: a decrease (1992-2001), followed by an increase (2001-2006), and then a progressive decrease (from 2006). The secular changes differed greatly according to age. Among females, these fluctuations were smaller, the decrease began earlier and was greater, and the subsequent increase was much smaller. Marriage was found to be less protective for Ethiopian immigrants than for the other surveyed populations. Conclusions The considerable gap between the EI's and FSUI's suicide rates highlights the critical role of immigrants' integration difficulties. These difficulties among EI lead to ongoing conflict within the family, which may explain why marriage is less protective for EI. Nevertheless, progressive integration is occurring as indicated by the decline in suicide rates since 2006. The fluctuations in EI suicide rates over time seem to be associated with modifications in social welfare allowances, which are crucial for EI of low socioeconomic status. Groups at risk, particularly EI men facing socioeconomic challenges and EI with considerable family conflict, typically identified by HMOs and welfare services, should be screened for suicide risk, and those identified as at risk referred to tailored workshops sensitive to Ethiopian culture.